CFTR Cl- channel and CFTR-associated ATP channel: distinct pores regulated by common gates. - Sugita, M (1998)
The cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride channel that is regulated by phosphorylation of the R domain and ATP hydrolysis at two nucleotide-binding domains (NBDs). It is controversial whether CFTR conducts ATP or whether CFTR might be closely associated with a separate ATP conductance. To characterize ATP channels associated with CFTR, we analyzed Cl- and ATP single channel-currents in excised inside-out membrane patches from MDCK epithelial cells transiently expressing CFTR. With 100 mM ATP in the pipette and 140 mM Cl- in the bath, ATP channels were associated with CFTR Cl- channels in two-thirds of patches that included CFTR. CFTR Cl- channels and CFTR-associated ATP channels had slope conductances of 7.4 pS and 5.2 pS, respectively, and had distinct reversal potentials and sensitivities to channel blockers. CFTR-associated ATP channels exhibited slow gating kinetics that depended on the presence of protein kinase A and cytoplasmic ATP, similar to CFTR Cl- channels. Gating kinetics of the ATP channels as well as the CFTR Cl- channels were similarly affected by non-hydrolyzable ATP analogues and mutations in the CFTR R domain and NBDs. Our results indicate that phosphorylation- and nucleotide-hydrolysis-dependent gating of CFTR is directly involved in gating of an associated ATP channel. However, the permeation pathways for Cl- and ATP are distinct and the ATP conduction pathway is not obligatorily associated with the expression of CFTR.